PENGARUH AKTIVATOR NAOH PADA ARANG TEMPURUNG KELAPA SEBAGAI MEDIA ADSORBEN PADA LIMBAH CAIR TAHU - Nur Alimah, Gustin; Khuzaimah, Siti; Ramadhani, Arnesya (Badan Perencanaan Pembangunan Penelitian dan Pengembangan Daerah Kabupaten Cilacap, 2024)
Activated charcoal is becoming more important as Indonesia's industrial sector expands. To meet this growing need, researchers and entrepreneurs in the activated charcoal industry must strike a balance between producing enough high-quality charcoal and meeting the growing demand for it. In order to find out how well activated coconut shell charcoal adsorbs tofu liquid waste, this research set out to do just that. Carbonation, activation, and data analysis were the procedures employed. Tofu liquid waste was effectively adsorbed using activated coconut shell charcoal with NaOH activator, according to the findings. An rise in the pH of the tofu liquid waste which was 4 before treatment and 6 after indicates this. The use of adsorbents when activated charcoal is mixed in an acid group solution is able to release H+ causing a decrease in pH. There was a difference in the color and scent markers both before and after the therapy. With 25% NaOH, the COD level is 643 mg/L, with 75% NaOH bringing it down to 365 mg/L. Similarly, with 25% NaOH, the BOD level is 300 mg/L, with 75% NaOH bringing it down to 250 mg/L. Lastly, with 25% NaOH, the TSS level is 116 mg/L, with 75% NaOH bringing it down to 102 mg/L. This demonstrates that the activated carbon may remove contaminants from the tofu liquid byproducts.